Impact of Scoring Balloons on Percutaneous Transluminal Angioplasty Outcomes in Femoropopliteal Lesions. (June 2020) - Horie, Kazunori; Tanaka, Akiko; Taguri, Masataka; Inoue, Naoto
Purpose: To investigate the efficacy of scoring balloons for immediate success of percutaneous transluminal angioplasty (PTA) in femoropopliteal lesions.Materials and Methods: Between 2013 and 2019, 398 consecutive patients with de novo femoropopliteal lesions were treated using PTA in our hospital. The procedure success rate was compared among patients undergoing PTA with vs without scoring balloons after 1:1 propensity score matching on hemodialysis, TransAtlantic Inter-Society Consensus II classification, Peripheral Arterial Calcium Scoring System (PACSS) grade, lesion length, and use of intravascular ultrasound. Propensity matching produced 84 patients (mean age 73.4±8.3; 65 men) treated with scoring balloons and 84 patients (mean age 75.6±8.7; 56 men) treated with plain balloons. Kaplan-Meier analysis investigated patency after the procedure in both groups; estimates are given with the 95% confidence interval (CI).Results: Residual stenosis <30% was achieved more often (77.4% vs 57.1%, p=0.005) and severe arterial dissection occurred less frequently (16.7% vs 29.8%, p=0.043) in the scoring balloon group vs the plain balloon group, respectively. The rate of provisional stenting was significantly lower after scoring balloon use (13.3% vs 29.8%, p=0.008). Multivariable analysis revealed that use of scoring balloons (p<0.001) and prolonged inflation time (p<0.001) were independent predictors of successful angioplasty, whereas chronic total occlusion (p=0.005) and longer lesion length (p=0.005) were predictors of an unsuccessful procedure. Among 108 patients with PACSS 0–3 lesions in the matched population, Kaplan-Meier analysis showed better primary patency at 18 months in the scoring balloon group in the intention to treat analysis [68.6% (95% CI 53.5% to 80.6%) vs 43.0% (95% CI 28.7% to 58.5%), p=0.044].Conclusion: Scoring balloons may be effective in restoring acute lumen gain and preventing severe arterial dissection in femoropopliteal lesions. Moreover, scoring balloons might be associated with better primary patency at 18 months in PACSS 0–3 lesions.